2020
DOI: 10.2196/14202
|View full text |Cite
|
Sign up to set email alerts
|

Capturing At-Home Health and Care Information for Children With Medical Complexity Using Voice Interactive Technologies: Multi-Stakeholder Viewpoint

Abstract: Digital health tools and technologies are transforming health care and making significant impacts on how health and care information are collected, used, and shared to achieve best outcomes. As most of the efforts are still focused on clinical settings, the wealth of health information generated outside of clinical settings is not being fully tapped. This is especially true for children with medical complexity (CMC) and their families, as they frequently spend significant hours providing hands-on medical care … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…However, limitations and concerns still exist about VA use in practice. Some limitations are the need for persistent internet connection, deficiencies in speech recognition and comprehension, the need for IT infrastructure for health system integration [e.g., electronic health record (EHR)], and Health Insurance Portability and Accountability Act (HIPAA) compliance to exchange personal health information 7,29 . In 2019, Amazon initiated HIPAA compliant VA services ("Alexa skills") 30 , yet, the implementations were limited to only some services and organizations.…”
Section: Current State Of Voice Assistantsmentioning
confidence: 99%
“…However, limitations and concerns still exist about VA use in practice. Some limitations are the need for persistent internet connection, deficiencies in speech recognition and comprehension, the need for IT infrastructure for health system integration [e.g., electronic health record (EHR)], and Health Insurance Portability and Accountability Act (HIPAA) compliance to exchange personal health information 7,29 . In 2019, Amazon initiated HIPAA compliant VA services ("Alexa skills") 30 , yet, the implementations were limited to only some services and organizations.…”
Section: Current State Of Voice Assistantsmentioning
confidence: 99%
“…We plan to interview non–English-speaking caregivers to understand their needs in medical communications, their challenges in using a traditional patient portal, and how a translation app could be seamlessly integrated into the existing channels of communication with their child’s care team. Our previous user-centered research has been successfully implemented [ 15 ], funded (eg, Challenges of the Health Resources and Service Administration’s Maternal and Child Health Bureau), and supported in complex care [ 16 , 17 ]. We will follow a similar strategy to engage end users and community members with our multidisciplinary stakeholder team.…”
Section: Methodsmentioning
confidence: 99%
“…The usability and acceptance of the app will be measured using scientific methods. Our team has an extensive track record in acceptability and usability testing [ 17 , 20 , 21 ]. We will be employing a user-centered, participatory design and testing methodology, and widely adopted usability and acceptance scales, such as the system usability scale (SUS) and the technology acceptance model (TAM) [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The latest advances in the field of artificial intelligence (AI) and natural language understanding have paved a way for the wide application of voice technology (VT) in health care through smart speakers and mobile apps. First real-world implementations have confirmed that AI conversational agents have the potential to support clinical care and optimize workflows [3,[11][12][13]. Nationwide Children's Hospital (in Columbus, Ohio) implemented voice technology for pediatric medicine [11], while Mayo Clinic developed Amazon's Alexa software to automatically answer COVID-19-related questions [12].…”
Section: Introductionmentioning
confidence: 99%
“…First real-world implementations have confirmed that AI conversational agents have the potential to support clinical care and optimize workflows [3,[11][12][13]. Nationwide Children's Hospital (in Columbus, Ohio) implemented voice technology for pediatric medicine [11], while Mayo Clinic developed Amazon's Alexa software to automatically answer COVID-19-related questions [12]. Furthermore, CardioCube software (CardioCube Corp.) deployed on Amazon Alexa was shown to be functional for paperless medical history collection from patients with CVD [3] as well as for long-term remote follow-up of individuals with HF at home [13].…”
Section: Introductionmentioning
confidence: 99%